Adercodon pleijeli gen. et sp. nov. (Polychaeta, Ampharetidae) from the Mediterranean Sea. In: J.-C. Dauvin, L. Laubier & D.J. Reish (Eds). Actes de la 4ème Conférence internationale des Polychètes. - Mackie, Andrew S.Y. (Mémoires du Muséum National d'Histoire Naturelle (Zoologie), 1994)
Adercodon pleijeli gen, et sp. nov. is described from muddy sediments (32-95 m depth) off Banyuls-sur-Mer, France and the east coast of Sicily, Italy. Characterised by 3 pairs of smooth branchiae, 13 thoracic setigers (paleae lacking), thoracic uncini from setiger 4 and papillose buccal tentacles the new form differs from all known ampharetid genera. Nevertheless, the possession of a ventral row of buccal teeth suggests an affinity with Gnathampharete Desbruyères, 1978. The arrangement and position of the teeth along the leading edge of the innermost ventral lip suggests that such teeth are functional and not an evolutionary remnant. Certain aspects of the taxonomy of the Ampharetidae are discussed.
AnnelidaBase